Early leaving from vocational education and training (ELVET) in Germany - Huismann, Adrienne [Verfasser]; Hippach-Schneider, Ute [Verfasser] (My University, 2023)
"This article first discusses the concept and understanding of dropping out of vocational education and training in general. It then presents the situation of early leaving from VET in Germany on the basis of the relevant available data on contract dissolution rates. Furthermore, the focus is on the preventive education policy measures that are intended to prevent drop-out as well as factors that can lead to early drop-out. An overview of developments during the COVID 19 pandemic concludes the article." (BIBB-Autorenreferat)
Keywords: G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); L 2 Lehr-Lerngestaltung; 370; Ausbildungsabbruch; Einflussfaktor; Ausbildungsabbrecher; Jugendlicher ohne Berufsabschluss; Vertragslösungsquote; Lernbedingungen; Pandemie